Guidelines for selective radiological assessment of inversion ankle injuries. Issue 6547 (6th September 1986) - Dunlop, M G; Beattie, T F; White, G K; Raab, G M; Doull, R I
Abstract : A prospective study was performed to establish definitive guidelines for selective use of radiography in the assessment of inversion ankle injuries. Five hundred patients were included, representing 3.2% of the workload of the department during the study period. There were 379 soft tissue injuries, 56 malleolar fractures, 40 avulsion fractures, 21 fractures at the base of the fifth metatarsal, and four calcaneal fractures. Multiple logistic regression identified distal fibular tenderness, age, and ability to bear weight as the most important clinical variables in predicting important fractures (p less than 0.001). A policy of requesting x ray examination of only those patients with distal fibular tenderness or inability to bear weight or aged over 60, with a further proviso that no foot radiographs should be obtained, would produce a 60% reduction in ankle radiography in this centre without detriment to patient care.